Analyzing the thermal regime of power supply units in portable betatrons by using infrared thermography; MATEC Web of Conferences; Vol. 92 : Thermophysical Basis of Energy Technologies (TBET-2016) - Simonova O. S. Olga Sergeevna; Kasyanov (Kas'yanov) V. A. Valery Alekseevich; Moskovchenko A. I.; Xingwang G. (2017, 2017)
Title screen